2019
DOI: 10.22331/q-2019-12-09-214
|View full text |Cite
|
Sign up to set email alerts
|

An initialization strategy for addressing barren plateaus in parametrized quantum circuits

Abstract: Parametrized quantum circuits initialized with random initial parameter values are characterized by barren plateaus where the gradient becomes exponentially small in the number of qubits. In this technical note we theoretically motivate and empirically validate an initialization strategy which can resolve the barren plateau problem for practical applications. The technique involves randomly selecting some of the initial parameter values, then choosing the remaining values so that the circuit is a sequence of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
294
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 379 publications
(295 citation statements)
references
References 61 publications
1
294
0
Order By: Relevance
“…point for the optimization of p + 1 layers and by setting α p+1 such that L p+1 (α p+1 ) is an identity. This strategy also avoids barren plateaus [27,28] and helps to mitigate the problem of local minima, as we discuss in Appendix C of Supplementary Material (SM). Next, we argue that C is closely connected to the accuracy of the eigensystem.…”
Section: Resultsmentioning
confidence: 99%
“…point for the optimization of p + 1 layers and by setting α p+1 such that L p+1 (α p+1 ) is an identity. This strategy also avoids barren plateaus [27,28] and helps to mitigate the problem of local minima, as we discuss in Appendix C of Supplementary Material (SM). Next, we argue that C is closely connected to the accuracy of the eigensystem.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, with an expressible circuit, choosing a random starting point for a VQE optimization is not a reasonable approach. Methods for circumventing this issue have been proposed, suggesting ways to improve the “optimizability” of a parameterized quantum circuit. These techniques indicate a tension between being expressible and being optimizable (i.e., having sufficient variation in the cost function).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to McClean et al 9 , who showed vanishing gradients for deep PQCs. They noted that randomly initializing θ for a V(θ) that forms a 2-design leads to a barren plateau, i.e., with the gradient vanishing exponentially in the number of qubits, n. Their work implied that researchers must develop either clever parameter initialization strategies 32,33 or clever PQCs ansatzes 4,34,35 . Similarly, our work implies that researchers must carefully weigh the balance between trainability and operational relevance when choosing C.…”
mentioning
confidence: 99%